Law, economics, and morality - Zamir, Eyal.; Medina, Barak (New York ; Oxford : Oxford University Press, 2010)
This work examines the possibility of combining economic methodology and deontological morality through explicit and direct incorporation of moral constraints into economic models.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Law and economics; Law -- Philosophy; Law -- Economic aspects; Economics -- Moral and ethical aspects; Law -- Moral and ethical aspects